False-Positive Dengue NS1 Antigen in Influenza and Other Febrile Illnesses - Ayaz, Khan Fariduddin Mohammad; Rahman, Mizanur; Rahim, Rummana; Hasan, Md Abu (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Abstrcat not available J Bangladesh Coll Phys Surg 2023; 41(4): 350-351